Comparing persistence of product and process innovation: A discrete-time duration analysis of innovation spells - David Córcoles; Ángela Triguero; María Carmen Cuerva (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
The main purpose of this paper is to analyse the influence of previous experience and learning capabilities on survival in product and process innovation for Spanish manufacturing firms in the period 1990-2010. The authors find past and path dependence and confirm the important effect of R&D effort in both types of innovation. Nevertheless, for product innovation, the level of appropriability and the fact of operating in a high-tech sector are more crucial for persistence in comparison with process innovation.
Keywords: O31; O32; L22; L60; 330; persistence in innovation; product innovation; process innovation; discretetime duration models; Spanish firms